Impacts of in vivo and in vitro exposures to tamoxifen: comparative effects on human cells and marine organisms - Fonseca, T. G. (2020)
Tamoxifen (TAM) is a first generation-SERM administered for hormone receptor-positive (HER+) breast cancer in both pre- and post-menopausal patients and may undergo metabolic activation in organisms that share similar receptors and thus face comparable mechanisms of response. The present study aimed to assess whether environmental trace concentrations of TAM are bioavailable to the filter feeder M. galloprovincialis (100 ng L-1) and to the deposit feeder N. diversicolor (0.5, 10, 25 and 100 ng L-1) after 14 days of exposure. Behavioural impairment (burrowing kinetic), neurotoxicity (AChE activity), endocrine disruption by alkali-labile phosphate (ALP) content, oxidative stress (SOD, CAT, GPXs activities), biotransformation (GST activity), oxidative damage (LPO) and genotoxicity (DNA damage) were assessed. Moreover, this study also pertained to compare TAM cytotoxicity effects to mussels and targeted human (i.e. immortalized retinal pigment epithelium - RPE; and human transformed endothelial cells - HeLa) cell lines, in a range of concentrations from 0.5 ng L-1 to 50 μg L-1. In polychaetes N. diversicolor, TAM exerted remarkable oxidative stress and damage at the lowest concentration (0.5 ng L-1), whereas significant genotoxicity was reported at the highest exposure level (100 ng L-1). In mussels M. galloprovincialis, 100 ng L-1 TAM caused endocrine disruption in males, neurotoxicity, and an induction in GST activity and LPO byproducts in gills, corroborating in genotoxicity over the exposure days. Although cytotoxicity assays conducted with mussel haemocytes following in vivo exposure was not effective, in vitro exposure showed to be a feasible alternative, with comparable sensitivity to human cell line (HeLa).